The Role of Social Presence Against Impulse Buying at TikTok Live Streaming Shop Consumers Based on S-O-R Framework (Open Society Conference, 2023)
This research aims to explore how social presence in Live streaming influences impulse buying through the emotional states of arousal and pleasure, based on the S-O-R (Stimulus-Organism-Response) framework. The object of this research is TikTok Live streaming Shop consumers aged 18 years and over. The data collection technique used is a questionnaire via google form. The sample used in this research was 200 respondents using the SEM method assisted by AMOS 22 software. The results showed that there was an influence of the social presence of broadcasters, the social presence of Live streaming on arousal and pleasure. While the results of the social presence of viewers on arousal have an effect, but have no effect on pleasure. Then the results of arousal and pleasure affect impulse buying of TikTok Live streaming Shop consumers. The benefit that can be obtained from the results of this research is that it can help TikTok live streamer to increase their sales by applying the concept of social presence and consumer emotional factors.  Because it can make sales on Live streaming more attractive and convenient for consumers.